Penggunaan Media Pembelajaran Interaktif dengan Aplikasi Quizizz untuk Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Fisika - Sri Jumini; Alifiyah Hidayatun; Sita Dewi; Fatiatun Fatiatun; Intan Masruroh; Deni Aryati (Universitas Hamzanwadi, 2022)
The purpose of the study was to increase students' motivation to learn physics by using interactive learning media based on the Quizizz game. Teachers in the 5.0 industrial revolution must be able to create fun and innovative learning by utilizing technological developments, without losing the essence and material that will be delivered by the teacher. This study uses a qualitative description method, which describes the implementation of interactive learning media using the Quizizz game to increase motivation to learn physics. The discussion focuses on the Physics quiz model in the Quizizz application and the results of the Quizizz game implementation. Based on the results of the study, it can be said that the application of the Quizizz game during learning increases students' learning motivation.